Stuart Croft returns - Croft, Stuart 1970-2015; Bennett, Emma; Leader, Darian; Levy, Deborah 1959- (The Everyday Press, 2024)
The first large published survey on the work of British artist Stuart Croft (1970-2015). This book describes in detail all of the film loops produced by the artist and filmmaker. Edited by Emma Bennett and produced in collaboration with the Stuart Croft Foundation
Keywords: Croft, Stuart -- 1970-2015